Lactiplantibacillus plantarum Reduced Renal Calcium Oxalate Stones by Regulating Arginine Metabolism in Gut Microbiota - Liu, Yu; Jin, Xi; Tian, Lei; Jian, Zhongyu; Ma, Yucheng; Cheng, Liang; Cui, Yaqian; Li, Hong; Sun, Qun; Wang, Kunjie (Frontiers in Microbiology, 2021)
Renal calcium oxalate (CaOx) stones are a common kidney disease. There are few methods for reducing the formation of these stones. However, the potential of probiotics for reducing renal stones has received increasing interest. We previously isolated a strain of Lactiplantibacillus plantarum N-1 from traditional cheese in China. This study aimed to investigate the effects of N-1 on renal CaOx crystal deposition. Thirty rats were randomly allocated to three groups: control group (ddH2O by gavage), model group (ddH2O by gavage and 1% ethylene glycol (EG) in drinking water), Lactiplantibacillus group (N-1 by gavage and 1% EG in drinking water). After 4 weeks, compared with the model group, the group treated with N-1 exhibited significantly reduced renal crystals (P < 0.05). In the ileum and caecum, the relative abundances of Lactobacillus and Eubacterium ventriosum were higher in the control group, and those of Ruminococcaceae UCG 007 and Rikenellaceae RC9 were higher in the N-1-supplemented group. In contrast, the relative abundances of Staphylococcus, Corynebacterium 1, Jeotgalicoccus, Psychrobacter and Aerococcus were higher in the model group. We also predicted that the arginase level would be higher in the ileal microbiota of the model group than in the N-1-supplemented group with PICRUSt2. The arginase activity was higher, while the level of arginine was lower in the ileal contents of the model group than in the N-1-supplemented group. The arginine level in the blood was also higher in the N-1-supplemented group than in the model group. In vitro studies showed that exposure to arginine could reduce CaOx crystal adhesion to renal epithelial HK-2 cells. Our findings highlighted the important role of N-1 in reducing renal CaOx crystals by regulating arginine metabolism in the gut microbiota. Probiotics containing L. plantarum N-1 may be potential therapies for preventing renal CaOx stones.